Population ecology of Cittarium pica (Gastropoda: Trochidae) of San Andrés Island, International Biosphere Reserve, Seaflower - Rico Mora, Jeimmy Paola (2017)
Cittarium pica is a conspicuous gastropod of the rocky coastlines of the Caribbean. Given its importance in the diet of Caribbean communities, it has been over-exploited, even reaching extinction in some places, and the species has been included in the red lists of marine invertebrates in some countries. Its fishery in San Andres Island-Colombia is artisanal without any regulation, leading to a decrease in its population. Taking into account the socio-economic, cultural and ecological importance of C. pica and its vulnerability to extinction, it is urgent to develop management actions directed to increase the resilience of the species and its sustainability as a fishery resource. To assess the current population state of C. pica from San Andrés Island, we estimated size structure, sex structure, maturation size, and growth parameters, based on length-frequency data analysis. From September to December 2013, and January to March 2014, we randomly collected 458 individuals at eight representative sites of the rocky shores of the island. We measured the longest diameter of the shell base, determined the sex by the color of the gonad, and thus determined the minimum maturation size. We found, that 80 % of the population consisted of small individuals < 25.5 mm sizes. The sex ratio was 1:1 except in November, where males were more abundant. The minimum size at the beginning of maturity for both sexes was 14.07 mm. The growth parameters of von Bertalanffy: K (0.730 yr-1), L∞ (110.78 mm) and Φ (3.95) were higher when compared to other populations of the Caribbean. The total mortality was 3.39 yr-1, while natural and fishing mortalities were 1.02 yr-1 and 2.36 yr-1, respectively. The maximum annual recruitment pulse was estimated for June, and the maximum exploitation rate for a sustainable yield was between 0.563 and 0.640, when the catch size was greater than 40 mm or 50 mm, respectively. The exploitation rate was estimated in 0.70, suggesting a strong extractive resource pressure. With these results we recommend the closure of the fishery and constant monitoring to promote and the population recovery is verified. Until a monitoring shows that the population recovers on the island.Until a monitoring shows that the population recovers on the island.